2015
DOI: 10.2174/1389203716666150330130102
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid: A Versatile Phytohormone in Plant Signaling and Beyond

Abstract: As sessile organisms, plants cannot escape from adverse conditions and, therefore, they have developed complex responses to the changing environment. Plant responses to abiotic cues involve changes in metabolism, photosynthesis, gene expression, ion levels, etc., and must be perfectly coordinated by phytohormones. The abscisic acid (ABA) is the main phytohormone involved in abiotic stress responses although it is nowadays clear that its signaling pathways are not isolated but interconnected with other hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 0 publications
1
49
0
Order By: Relevance
“…While ABA repression of ilp3 and ilp4 transcript levels in the A. stephensi midgut was consistent with the effects of ABA on P. falciparum infection, our previous studies of these peptides [13] as well as observed effects of ABA on mammals and plants [3336] suggested that ABA may have broader effects on A. stephensi physiology. A major target of IIS is phosphorylation and inhibition of GSK-3, a pivotal mediator of metabolism, inflammation, cell death, and survival in mammalian cells [37].…”
Section: Resultssupporting
confidence: 83%
“…While ABA repression of ilp3 and ilp4 transcript levels in the A. stephensi midgut was consistent with the effects of ABA on P. falciparum infection, our previous studies of these peptides [13] as well as observed effects of ABA on mammals and plants [3336] suggested that ABA may have broader effects on A. stephensi physiology. A major target of IIS is phosphorylation and inhibition of GSK-3, a pivotal mediator of metabolism, inflammation, cell death, and survival in mammalian cells [37].…”
Section: Resultssupporting
confidence: 83%
“…ABA is considered the primary hormone involved in regulation of plant responses to abiotic stresses, especially drought32. ABA levels were observed to increase in both roots (all tested plant combinations) and leaves (except for RL) (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Most of the plant responses to these abiotic conditions are mediated by abscisic acid. The ABA-signaling pathway is initiated by its binding to the specific receptor complex RCARs/PYR1/PYLs, leading to inactivation of type 2C protein phosphatases and activation of kinases, which mediate ABA-dependent changes in metabolism, gene expression, and ion channel activity (3, 4). …”
Section: Introductionmentioning
confidence: 99%